Abstract 173: A Case Series of Basilar Tip Aneurysm Endovascular Treatment – The Barrow Neurological Institute Experience - Yasmin G. Ghochani (Stroke: Vascular and Interventional Neurology)
Introduction Basilar‐tip aneurysm (BTA) is the most common aneurysm found in the posterior circulation, representing 5–8% of total intracranial aneurysms. Endovascular techniques are first‐line for treatment of the vast majority of posterior circulation artery aneurysms because of their deep location and the high mortality and morbidity associated with microsurgical clipping. Coil embolization (CE) is safer and more efficacious in the treatment of BTAs compared to open surgery but has increased rate of recanalization. Two adjunctive modifications of CE ‐ balloon remodeling techniques (BRT) and stent‐assisted coiling (SAC) ‐ have been utilized to facilitate occlusion of BTAs of variable anatomies/morphologies, sizes, and rupture status. We aimed to compare the clinical utility, safety and efficacy of these adjuvant therapies for treating BTAs. Methods A retrospective secondary analysis of a prospectively collected database at our institution was performed, including all patients with endovascularly treated basilar tip aneurysms database from January 1996 through January 2019 (n=121; CE=26; BRT=51; SAC=44). This project was approved by the local institutional review board. Patient data on demographics, aneurysmal characteristics and management, post‐operative outcomes, ICU management, and withdrawal of care were abstracted from the medical record of eligible patients. Univariate statistics used Welch’s two‐sample t‐test for continuous data and chi‐squared test for frequency‐based variables. Multivariate analysis used multivariate Poisson and Firth’s logistic regression. Results Aneurysms treated with CE were found to be smaller compared to BAC and SAC, with a median difference of 4 mm. For ruptured aneurysms, Adjuvant therapy (BAC or SAC) was used to treat larger dimension aneurysms compared to CE (p = 0.046). Adjusted for other factors, aneurysm dimension was an independent factor influencing recanalization or recurrence (OR = 1.16, p = 0.006), retreatment (OR = 1.165, p = 0.005), and obliteration (Raymond Roy Grade, continuous, β = 0.033, p = 0.043). Ruptured aneurysms were most frequently treated with CE (80.8%), followed by BAC (47.1%), and least frequently with SAC (6.8%) (p < 0.001). We also found an association with time of approval to retreatment. Stents approved by FDA after 2014 (used in 13 cases) had a greater rate of retreatment (46.2% vs. 10.7%). Adjusted for other factors, BAC had 3 times greater odds of recanalization or recurrence compared to SAC. CE demonstrated a 1.19‐month greater time to retreatment than BAC and a 1.89‐month longer time to retreatment than SAC. Overall, CE had a 1.28‐month greater time to retreatment than adjuvant therapy (SAC or BAC). Conclusion CE and its adjuvant therapies have similar safety profile but pose variable efficacy in terms of obliteration, recurrence, retreatment, and durability over time. This study represents one of the largest data sets on endovascular adjuvant therapy of BTAs and has the potential to inform clinical decision making when considering CE with BRT vs. SAC for BTA of specific size and morphology. In the future, inclusion of BTAs treated with WEB device and more novel flow divertor devices in this data set can further inform clinical decision making.